2015
DOI: 10.1039/c4ra12291g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of mesoporous silica nanospheres with radially oriented mesochannels by microemulsion templating for adsorption and controlled release of aspirin

Abstract: The MSN spheres with narrow size distribution and radially oriented mesoporous channels were prepared using an O/W microemulsion system, consisting of CTAB (or PVP), ethanol, cyclohexane and water as template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…8 So far, hollow spherical silica capsules have been used as containers for a variety of drugs such as ibuprofen, doxorubicin and aspirin. [9][10][11] Recently, Huang et al have demonstrated that silica particles with a higher aspect ratio are preferentially taken up by cells compared to spherical silica particles of similar size due to an increased contact area between the longitudinal side of the particles and the cell membrane. 12 Chen et al have shown that elongated HMSC could be effectively used for the transport and release of therapeutics, such as doxorubicin for the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…8 So far, hollow spherical silica capsules have been used as containers for a variety of drugs such as ibuprofen, doxorubicin and aspirin. [9][10][11] Recently, Huang et al have demonstrated that silica particles with a higher aspect ratio are preferentially taken up by cells compared to spherical silica particles of similar size due to an increased contact area between the longitudinal side of the particles and the cell membrane. 12 Chen et al have shown that elongated HMSC could be effectively used for the transport and release of therapeutics, such as doxorubicin for the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The PVP molecule chains were adsorbed on CTAB cylindrical O/W (oil-in-water) microemulsion droplets, forming a continuous layer similar to a capping agent, to inhibit the growth of microemulsion droplets in all directions. The presence of the amount of PVP molecules could have stabilized the microemulsion droplets during the reaction and led to the formation of uniform smaller particles [31]. After hydrolysis reaction of TEOS and solvothermal process, WSNs with a wrinkled, highly ordered, radially oriented mesochannels can be formed.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, MSNs with radiation-aligned mesopores (the pores of silica nanoparticles are mesoporous with large centerradial pore channels in random orientations) are found to have promising biomedical and catalytic applications for immobilizing some guest molecules such as enzymes, which allow active catalytic sites to disperse onto large internal surfaces and pores, which in turn improve the activity of catalyst system [28][29][30]. We demonstrated that MSNs with ordered mesochannels aligned perpendicular to the sphere surface could be used as multifunctional carriers in drug delivery, and that the unique pore configuration is more suitable for regulating diffusional loading and release from radially oriented mesochannels [31].…”
Section: Introductionmentioning
confidence: 95%
“…However, the controlled-release time was less than 150 min. The methodology of using hierarchical pores to improve both drug loading and sustained release rate was also reported by Pang et al 57 In their ASA carrier system, mesoporous silica nanospheres with radially oriented mesochannels were fabricated. Datt et al 48 studied ASA loading and release from hollow silica nanoparticles functionalized with aminopropyl groups via co-condensation or post-synthesis modification methods and determined ASA loading capacity ranging from 10% to 17% with a delivery time of less than 50 min.…”
Section: Amino Functionalization Of Smt and Drug Delivery Profilementioning
confidence: 88%
“…Therefore, SMTs template directed with CA electrospun fibers and CTAB combine both the advantages of hollow and mesoporous materials for a high drug loading capacity and sustained release profile. The methodology of using hierarchical pores to improve both drug loading and sustained release rate was also reported by Pang et al 57 In their ASA carrier system, mesoporous silica nanospheres with radially oriented mesochannels were fabricated.…”
Section: Amino Functionalization Of Smt and Drug Delivery Profilementioning
confidence: 88%